Tumor Necrosis Factor (TNF) Receptor Expression Determines Keratinocyte Fate upon Stimulation with TNF-Like Weak Inducer of Apoptosis. (5th December 2019) - Wang, Xuening; Cheng, Dan; Hu, Guanglei; Liang, Lili; Tan, Fei; Xiao, Tong; Xiao, Shengxiang; Xia, Yumin
Abstract : The interaction between tumor necrosis factor- (TNF-) like weak inducer of apoptosis (TWEAK) and fibroblast growth factor-inducible 14 (Fn14) regulates the fate of keratinocytes, depending on the relative expression of TNF receptor (TNFR) 1 or TNFR2. However, the precise mechanism underlying this TWEAK-mediated regulation remains unclear. The aim of this study was to provide comprehensive insight into the roles of Fn14, TNFR1/2, and other relevant molecules in the fate of keratinocytes. Further, we sought to elucidate the structural basis for the interaction of TWEAK and Fn14 in regulating cellular outcomes. Normal keratinocytes (mainly expressing TNFR1) and TNFR2-overexpressing keratinocytes were stimulated with TWEAK. Through immunoprecipitation and Western blotting of keratinocyte lysates, we elucidated the associations between Fn14, TNFR-associated factor 2 (TRAF2), cellular inhibitor of apoptosis protein 1 (cIAP1), and TNFR1/2 molecules. Additionally, we found that TRAF2 exhibited binding to Fn14, cIAP1, and TNFR1/2. Our data suggest that TWEAK induces apoptosis in normal keratinocytes and proliferation in TNFR2-overexpressing keratinocytes in a TNF- α -independent manner; however, inhibition of TRAF2 appears to reverse this effect. Interestingly, the interaction between TWEAK and Fn14 increased TNFR1-associated death domain protein and caspase-8 expression in normal keratinocytes and promoted cytoplasmic import of cIAP1 in TNFR2-overexpressing keratinocytes. In conclusion, we found that the Fn14-TRAF2-TNFR signaling axis mediates TWEAK's regulation of the fate of keratinocytes, possibly in a manner involving the TNF- α -independent TNFR signal transduction.